The Impact of Oil Price Shocks on Economic Growth - Iraq A Case Study for The Period (1968 - 2019) Using Symmetric and Asymmetric Co-Integration Analysis - Rizgar Abdlkarim Abdlaziz ,; Yaseen Abdulrahman Ahmed,; Burhan Ali Mohammed,; Kamaran Qader Yaqub, (QALAAI ZANIST JOURNAL, 2022)
This study investigates the symmetry and asymmetry impact of oil price shocks on economic growth for the Iraqi economy during 1968-2019. For this purpose, we utilizing Linear Autoregressive Distributed Lag (ARDL) and Nonlinear Autoregressive Distributed Lag (NARDL). The linear and nonlinear ARDL found that oil price shocks have a positive long-run impact on economic growth, as the F statistics are greater than the critical upper bound in all models. Moreover, the results of NARDL estimators show the asymmetry evidence: the oil price increases(LROILP+) have a greater and significant positive impact on real GDP per capita, While oil Price decrease coefficients(LROILP-) are insignificant and smaller than the oil price increase(LROILP+). That means an increase in oil price leads to raises in real GDP per capita. Consequently, the Iraqi economy and its Standard of living in terms of GDP per capita are sensitively affected by oil price changes due to the strong tide with world oil price changes. Then, diversify of the Iraqi economy, only the best choice in front of policymakers.